Shelf-life studies on blanched, dried pili nut - Piedad, Fay Ventura; Domningo-Dumelod, Benelyn G. (1995.)
The study aimed to determine the effectivity of steam-blanching prior to drying for prolonging shelf-life of pili kernel. The first phase involved the determination of optimum drying time for unblanched and steam-blanched pili kernels for 3, 6, and 9 minutes. The second phase dealt with the determination of sorption properties and critical moisture contents for every pili sample group. The final phase dealt with shelf-life estimation on pili samples sealed in 0.003-inch thick polypropylene bag. For the unblanched pili kernel sample, optimum drying time was determined to be 4 1/2 hours at 60°C to reach a moisture content (dry basis) of 2.43Sorption isotherm data showed that at aw levels above 0.85 to 1.00, the sample was prone to microbial attack due to absorption of moisture by the sample. At lower aw, deterioration may be caused by randicity. The sample's initial moisture content was found to be its critical moisture content since there were indications of incipient rancidity in the product prior to storage. However, it only becomes microbially unstable at moisture content of 4.50%. The estimated shelf-life of unblanched pili kernel sealed in a 0.003-inch polypropylene bag is 50 days. The optimum drying time for pili kernel steam-blanched for 3 minutes was 4 hours at 60°C. It was determined to be microbially unstable at aw above 0.85 ro 1.00 and prone to rancidity at lower aw. Critical moisture content is at its initial moisture content which was 2.44%. It is only prone to microbial attack at moisture content 4.84% or higher. The calculated shelf-life value of the 3-minute blanched pili kernels packed in 0.003-inch thick polypropylene bag is 48 days. Pili kernel steam-blanched for 6 minutes was dried to a moisture content of 2.48 % in 6 1/2 hours at 60°C. It was determined to be microbially unstable at aw above 0.85 to 1.00. Below this aw range, rancidity may occur. At its initial moisture content, there were indications of deterioration, thus considered the critical moisture content of the samples. At moisture content of 4.22%, the sample becomes microbially unstable. The estimated shelf-life of the 6-minute blanched pili kernels packed in 0.003-inch polypropylene bag is 30 days. Pili kernel steam-blanched for 9 minutes was dried to a moisture content of 2.53% in 8 1/2 hours at 60°C. It was determined to be microbially stable at aw 0.85-1.00 and at a moisture content of 4.00%. Indications of deterioration were observed at 2.53% moisture content at aw below 0.85. The estimated shelf-life value is 12 days for the 9-minute blanched pili kernels packed in 0.003-inch thick polypropylene bag. The experiment showed that steam-blanching of pili kernels may not be an effective method in lengthening shelf-life since it attributes additional moisture to the sample that may promote hydrolytic rancidity during drying.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Pili nut -- Storage